The Impact of Audit Findings and Follow-Up on Recommendations on Audit Opinion: A Study of Local Governments in Districts/Cities in Central Sulawesi Province - ZULHAERINI, Adilah; DIN, Muhammad; JURANA, Jurana; MUSTAMIN, Mustamin (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to determine the effect of internal control system weaknesses (KSPI), non-compliance with laws and regulations (KPTHN), and follow-up on audit recommendations (TLRHP) on local government audit opinions in Central Sulawesi Province for the 2019-2023 period. This study uses a quantitative approach with secondary data. The research sample consisted of 13 district / city governments in Central Sulawesi Province with a total sample of 65. Data analysis using WarpPLS 7.0 software. The analysis results show that TLRHP has a significant positive impact on audit opinion, while SPI weakness and KPTHN have a significant negative impact. These results indicate that strengthening the internal control system, improving conformity with laws and regulations, and optimizing the implementation of audit recommendations are critical to improving the accountability and quality of local government financial reports